Using Data Crawlers and Semantic Web to Build Financial XBRL Data Generators: The SONAR Extension Approach - Miguel Ángel Rodríguez-García; Alejandro Rodríguez-González; Ricardo Colomo-Palacios; Rafael Valencia-García; Juan Miguel Gómez-Berbís; Francisco García-Sánchez (The Scientific World Journal)
Precise, reliable and real-time financial information is critical for added-value financial services after the economic turmoil from which markets are still struggling to recover. Since the Web has become the most significant data source, intelligent crawlers based on Semantic Technologies have become trailblazers in the search of knowledge combining natural language processing and ontology engineering techniques. In this paper, we present the SONAR extension approach, which will leverage the potential of knowledge representation by extracting, managing, and turning scarce and disperse financial information into well-classified, structured, and widely used XBRL format-oriented knowledge, strongly supported by a proof-of-concept implementation and a thorough evaluation of the benefits of the approach.